Multi-Scale Climate Variability in Nova Scotia During the Past Century - McCartin, Chantal (Université d'Ottawa / University of Ottawa, 2017)
A study of the Nova Scotia surface air temperature over the last century (1900 to 2015) shows that internal variability on inter-annual, decadal and multi-decadal time scales can be partly explained by ocean-atmospheric climate modes, external and anthropogenic forcings. The Atlantic Multidecadal Oscillation (AMO) and Arctic Oscillation (AO) are shown to be the dominant climate drivers in Nova Scotia. The El Niño Southern Oscillation (ENSO) is also shown to be a dominant climate driver but only during the summer. Multivariate models were generated over the full time period using only natural ocean-atmospheric modes of variability but could not explain the rapid increase in the recent rate of warming (post-1980). The inclusion of anthropogenic greenhouse gas forcing to the models improved their predictive power annually and seasonally. The modelling results show that 11% of the annual variability in Nova Scotia results from natural forcings along with anthropogenic greenhouse gas forcing while seasonally up to 28% of the temperature variability can be explained by natural plus greenhouse gas forcings. The annual and seasonal low explained variance suggests that Nova Scotia is poorly modulated by climate indices, specifically during the winter, the time when relationships between ocean-atmospheric modes and the regional climate should be the strongest. It leads to believe that Nova Scotia is located in a transition zone where large-scale ocean-atmospheric modes of variability are transitioning from being positively correlated in a region to being negatively correlated in another region. The results of this study help to better understand how large-scale ocean-atmospheric modes of variability, external and anthropogenic greenhouse gas forcings affect Nova Scotia’s surface air temperatures and also provide insight into future potential variability under a changing climate.
Keywords: Nova Scotia; Teleconnections; Oceanic-atmospheric climate modes; Climate; Climate Change; Greenhouse Gas; Atlantic Multidecadal Oscillation; Arctic Oscillation; The El Niño Southern Oscillation; External forcing